2003
DOI: 10.1111/j.1348-0421.2003.tb03436.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Signaling of IFN‐γ in the Conjunctiva between Lewis and Brown Norway Rats

Abstract: Genetic background determines the histological features of experimental immune‐mediated blepharoconjunctivitis (EC) in rats, which is a model for human allergic conjunctivitis (AC). A great number of lymphocytes predominate in EC of Lewis rats, while less lymphocytes and more eosinophils are present in that of Brown Norway (BN) rats. Although this difference could be attributed to their systemic Th1/Th2 dominancy, it remains unclear whether some regulatory mechanisms may exist in the inflammatory site in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…cDNA was reverse transcribed and amplified using the SuperScript ™ III One‐Step RT‐PCR System with Platinum ® Taq DNA Polymerase (Invitrogen Corporation, San Diego, CA, USA). The following primer pairs (including the PCR product size in parentheses) were synthesized by Invitrogen (18–20): interleukin‐1alfa, 5′‐CTA AGA ACT ACT TCA CAT CCG CAG C‐3′ and 5′‐CTG GAA TAA AAC CCA CTG AGG TAG G‐3′ (623 bp); tumor necrosis factor‐alfa, 5′‐CAC GCT CTT CTG TCT ACT GA‐3′ and 5′‐GGA CTC CGT GAT GTC TAA GT‐3′ (616 bp); interleukin‐6, 5′‐CAA GAG ACT TCC AGC CAG TTG C‐3′ and 5′‐GGA GAA AGC TTC CCA ACT TTT G‐3′ (335 bp); and beta‐actin, 5′‐TTG TAA CCA ACT GGG ACG ATA TGG‐3′ and 5′‐GAT CTT GAT CTT CAT GGT GCT AGG‐3′ (759 bp). Cycling conditions for denaturation, annealing and extension were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was reverse transcribed and amplified using the SuperScript ™ III One‐Step RT‐PCR System with Platinum ® Taq DNA Polymerase (Invitrogen Corporation, San Diego, CA, USA). The following primer pairs (including the PCR product size in parentheses) were synthesized by Invitrogen (18–20): interleukin‐1alfa, 5′‐CTA AGA ACT ACT TCA CAT CCG CAG C‐3′ and 5′‐CTG GAA TAA AAC CCA CTG AGG TAG G‐3′ (623 bp); tumor necrosis factor‐alfa, 5′‐CAC GCT CTT CTG TCT ACT GA‐3′ and 5′‐GGA CTC CGT GAT GTC TAA GT‐3′ (616 bp); interleukin‐6, 5′‐CAA GAG ACT TCC AGC CAG TTG C‐3′ and 5′‐GGA GAA AGC TTC CCA ACT TTT G‐3′ (335 bp); and beta‐actin, 5′‐TTG TAA CCA ACT GGG ACG ATA TGG‐3′ and 5′‐GAT CTT GAT CTT CAT GGT GCT AGG‐3′ (759 bp). Cycling conditions for denaturation, annealing and extension were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was reverse transcribed and amplified using the SuperScript™ III One‐Step reverse transcription–polymerase chain reaction (RT–PCR) System with Platinum® Taq DNA Polymerase (Invitrogen). Based on previous reports (20,21), the following primer pairs (including PCR product size in parentheses) were synthesized by Invitrogen: interleukin‐1β, 5′‐AAG CTC TCC ACC TCA ATG GAC AG‐3′ and 5′‐CTC AAA CTC CAC TTT GCT CTT GA‐3′(260 bp); tumor necrosis factor‐α (TNF‐α), 5′‐CAC GCT CTT CTG TCT ACT GA‐3′ and 5′‐GGA CTC CGT GAT GTC TAA GT‐3′ (616 bp); IFN‐γ, 5′‐ATC TGG AGG AAC TGG CAA AAG GAC G‐3′ and 5′‐CCT TAG GCT AGA TTC TGG TGA CAG C‐3′ (288 bp); and β‐actin, 5′‐TTG TAA CCA ACT GGG ACG ATA TGG‐3′ and 5′‐GAT CTT GAT CTT CAT GGT GCT AGG‐3′ (759 bp). Cycling conditions for denaturation, annealing and extension were as follows: IL‐1β, 35 cycles of 94°C for 60 s, 58°C for 45 s and 72°C for 45 s; TNF‐α, 35 cycles of 94°C for 60 s, 58°C for 45 s and 72°C for 45 s; IFN‐γ, 40 cycles of 94°C for 60 s, 58°C for 45 s and 72°C for 45 s; and β‐actin, 35 cycles of 94°C for 60 s, 58°C for 45 s and 72°C for 45 s. PCR was performed with an iCycler™ (Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, by using experimental AC (EC) in rats [2,3,4] and mice [5, 6], we previously demonstrated that antigen (Ag)-primed CD4+ T cells play a crucial role in the infiltration of eosinophils into the conjunctiva. Although CD4+ T cells play the most prominent role in the development of EC, other types of immunocompetent cells also appear to participate.…”
Section: Introductionmentioning
confidence: 99%